ANALISIS DAYA DUKUNG LINGKUNGAN PERAIRAN TERHADAP DAYA TARIK WISATA DI KECAMATAN AJIBATA KABUPATEN TOBA SAMOSIR (The analysis of Waterworks Carrying Capacity to Tourist Attactions in Ajibata District Toba Samosir) - Enzelia R Gultom; Hesti Wahyuningsih; Yoes Soemaryono (AQUACOASTMARINE, 2017)
Ajibata is one of the tourist area in Lake Toba travelers who declined significantly in recent years.The objectives of this research are determining the effect of the presence of ferry ports and floating net cages to the carrying capacity of the Ajibata waterworks tourist area, knowing the environmental suitability as a tourist destination and knowing the perception of tourists to the carrying capacity of the waterworks environment. The research was conducted from April-May 2016 in Ajibata district which was divided into three (3) stations. The existence of ferry port and floating net cage aquaculture activities have an impact on tourism activities seen through the content of nitrate and phosphate on all respectively < 0.50 and 0.01. Ajibata tour area is still quite suitable as a tourist area with suitability index of 66.66%. Carrying capacity region with the area of 15.476 m2 which is 767 people/day. Tourist adequate attraction of Ajibata tour area seen from the perception of tourists that are 66.66% stated a slight smell, brown waters of 78.57%, 38.46% dissatisfied in touring, lack of tourist facilities 83.33%, 53.84% stated quite comfortable, the accessibility stated as quite easy as much as 66.66%, and 69.23% stated beautiful, so Ajibata is less attractive as the tourist destination to be visited.Keywords: Capability Areas, Tourist Attractions, Keramba Cage, Travel Suitability Index, Ferry Ports